A STATE OF KNOWLEDGE ABOUT GENDER STEREOTYPE AND FEMALE INVISIBILITY IN SCIENCE EDUCATION - de Abreu Fochesato Quidigno, Raquel; Roberto Dalmo Varallo Lima de Oliveira; Sérgio Camargo; Tania Teresinha Bruns Zimer (Revista Gênero e Interdisciplinaridade, 2021)
In recent years, the approach on the theme of the presence of women in the science is noticeable, as well as the importance of giving visibility to the history and the achievements of these scientists. However, obstacles to the female presence in the scientific field, such as sexism and the conception of an androcentric Science, discourage girls and women from entering and staying in the area. This research aims to build a state of knowledge about studies about gender stereotype, female invisibility, and the presence of women in Sciences, in works presented in the last five editions of ENPEC. Based on the analysis of 26 papers, the need to address the gender theme was notable, especially about the presence of women in Science early in Basic Education, aiming at equity between genders for the promotion of Education in Human Rights.